Bezoars: diagnosis, management, and potential complications in patients with psychiatric disorders - Cisneros Arias, Francisco De Jesús; Espinal Campa, Kassandra Janeth; Espinal Campa, Alondra Yaneli; Beltran Serrano, Erick; Diarte Vega, Hector Aurelio (International Journal of Research in Medical Sciences, 2023)
Word "bezoar" comes from Persian "pâdzahr," which means "antidote," since, in ancient times, it was believed that bezoar could cure and nullify effects of all poisons. In medical context, bezoar is the term used for conglomerates of undigested material that accumulate in de gastrointestinal tract. Case of 60-year-old female patient with repeated episodes of intestinal obstruction associated with digestive tract bleeding. She presented to emergency department with severe abdominal pain and intolerance to oral route. Computed tomography identified hypodense image suggestive of a oreign body in the small bowel lumen. During laparotomy, stone-like mass of approximately 3×5 cm was found at level of jejuno-ileal junction, 80 cm from Treitz ligament, with presence of an intestinal flange that conditions rotation of the intestinal loop on its axis. Intestinal obstruction due to bezoar is uncommon in adult patients, and symptoms are usually non-specific. It requires a high index of suspicion and effective screening for trichotillomania. In such cases, imaging studies such as tomography help to establish the diagnosis.